2022
DOI: 10.1002/tox.23619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a phthalate metabolite mixture on both normal and tumoral human prostate cells

Abstract: Phthalates represent a group of substances used in industry that have antiandrogenic activity and are found in different concentrations in human urine and plasma. More than 8 million tons of phthalates are used each year, predominantly as plasticizers in polyvinyl chloride (PVC) products. Phthalates are widely used in everyday consumer products and improperly discarded into the environment. Furthermore, in vivo studies carried out in our laboratory showed that a mixture of phthalates, equivalent to the mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
(124 reference statements)
2
7
0
Order By: Relevance
“…Our previous results showed that maternal exposure to a phthalate mixture altered the expression of microRNAs in the ovary and ventral prostate of rat offspring 15,18 . Likewise, phthalate monoester mixture exposure modulated benign and tumor human prostate cells and increased the expression of the miR‐184 and miR‐141‐3p in vitro 37 . The results presented here agreed with the microRNA sequencing profile presented by Scarano et al 15 and were correlated with some oncogenic targets by in silico analysis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our previous results showed that maternal exposure to a phthalate mixture altered the expression of microRNAs in the ovary and ventral prostate of rat offspring 15,18 . Likewise, phthalate monoester mixture exposure modulated benign and tumor human prostate cells and increased the expression of the miR‐184 and miR‐141‐3p in vitro 37 . The results presented here agreed with the microRNA sequencing profile presented by Scarano et al 15 and were correlated with some oncogenic targets by in silico analysis.…”
Section: Discussionsupporting
confidence: 90%
“…15,18 Likewise, phthalate monoester mixture exposure modulated benign and tumor human prostate cells and increased the expression of the miR-184 and miR-141-3p in vitro. 37 The results presented here agreed with the microRNA sequencing profile presented by Scarano et al 15 and were correlated with some oncogenic targets by in silico analysis. Furthermore, our results showed that the perinatally phthalate exposure can modify the rno-miR-184 expression in the prostate up to the F2 generation.…”
Section: Discussionsupporting
confidence: 90%
“…Phthalates have been detected in human blood, milk, and urine [ 66 , 79 , 80 ]. Several studies have identified a direct relationship between the exposure to phthalates and pathologies of different organs and systems such as metabolic disorders, damage to the reproductive system, and hormone-sensitive cancers [ 54 , 80 , 81 ], including breast cancer [ 66 , 82 ]. However, the relationship between phthalate and prostate gland pathologies needs further investigation [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that DEHP-induced fluctuations of estrogen and androgen levels might underlie the predisposition of prostatic enlargement. In industrialized countries, benign and malignant prostate disorders are among the most common diseases in men [ 53 , 54 ]. Worldwide, PCa represents the second-most common solid tumor in men [ 25 , 55 ], being the second-most prevalent global cancer in 2020, with the sixth highest cancer mortality rate, and accounting for up to 7.3% of all global cancer incidence [ 6 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation